Catalytic activity of supra molecular self-assembled Nickel (II) coordination complex in synthesis of indeno-pyrimidine derivatives. (15th January 2019) - Gangu, Kranthi Kumar; Maddila, Suresh; Mukkamala, Saratchandra Babu; Jonnalagadda, Sreekantha B.
Graphical abstract: This communication details the hydrothermal synthesis of [Ni2 (2, 6-pydc)2 (μ-4, 4′bpy)(H2 O)4 ].2H2 O, a versatile supramolecular 3D architecture. The two Ni(II) metal centres are connected through 4, 4′-bipyridine ligand. Unsaturated metal centres of Ni(II) acted as Lewis acidic sites showing excellent catalytic activity towards synthesis of indeno-pyrimidine derivatives. Abstract: A supra molecular self-assembled Ni(II) coordination complex, formulated as [Ni2 (2, 6-pydc)2 (μ-4, 4′bpy)(H2 O)4 ].2H2 O (2, 6-pydc: pyridine-2, 6-dicarboxylic acid, 4, 4′bpy:4, 4′-bipyridine) was synthesized under hydrothermal condition and characterized by single crystal X-ray diffraction, elemental analysis, FT-IR, powder X-ray diffraction and thermo gravimetric analysis. Single crystal X-ray diffraction analysis reveals that the complex crystallizes in the monoclinic space group P21 /c with cell parameters a = 10.5237(6) Å, b = 20.1966(10) Å, c = 7.2366(4) Å, β = 106.96(1°), V = 1471.22(314) Å 3 and displays a 3D supramolecular network through hydrogen bond and C–H⋯π, C–O⋯π interactions. Nickel(II) metal species in the structure possess coordinately unsaturated centers, which exhibited viable catalytic properties in the synthesis of five different indeno-pyrimidine derivatives through one-pot reaction involving aldehyde, indane-1, 3-dione and guanidinium chloride in a green approach. With the reaction achieved in 15 min time interval in ethanol in excellent yields (87–98%), plus the good recyclability (up to 6 times) provides advantage to this complex in heterogeneous catalysis.